Non-linear excitation of polariton cavity modes in ZnO single nanocombs - Capeluto, Maria Gabriela (2014)
Tunable second harmonic (SH) polaritons have been efficiently generated in ZnO nanocombs, when the material is excited close to half of the band-gap. The nonlinear signal couples to the nanocavity modes, and, as a result, Fabry-Pérot resonances with high Q factors of about 500 are detected. Due to the low effective volume of the confined modes, matter-light interaction is very much enhanced. This effect lowers the velocity of the SH polariton in the material by 50 times, and increases the SH confinement inside the nanocavity due to this higher refractive index. We also show that the SH phase-matching condition is achieved through LO-phonon mediation. Finally, birrefringence of the crystal produces a strong SH intensity dependence on the input polarization, with a high polarization contrast, which could be used as a mechanism for light switching in the nanoscale.